Path‐Dependent Evolution Versus Intentional Management of Investment Ties in Science‐Based Entrepreneurial Firms. (16th January 2013) - Vanacker, Tom; Manigart, Sophie; Meuleman, Miguel
<x xml:space="preserve">Abstract</x> This paper studies the role of entrepreneurs in investment tie formation in science‐based entrepreneurial firms. Specifically, we address why investment tie formation is path dependent for some firms but more amenable to intentional management for others. Using longitudinal case studies, our evidence suggests that early investment tie formation is path dependent because scientific entrepreneurs typically approach only one or a few prospective investors from within their institutional context. Differences in experience between early investors affect the professionalization of entrepreneurial teams (or lack thereof), which influences the extent to which subsequent investment tie formation becomes more amenable to intentional management or remains path dependent.